Carbon dioxide in non-aqueous solvents at pressures less than 200 KPA - Fogg, Peter G. T.; Clever, H. Lawrence (Solubility data series, 1992)
Carbon Dioxide in Non-aqueous Solvents at Pressures Less Than 200 KPA.